Pattern of Dermatological Diseases During the Lockdown and Pre-COVID Period at a Tertiary Care Center in Nepal - Gyawalee, Madhu; Kafle, Monique; Amatya, Amit; Kayastha, Bhaskar Mohan (Nepal Journal of Dermatology, Venereology & Leprology, 2022)
Introduction: Coronavirus disease 19 (COVID-19), which started in China, affected many countries in a short time and spread globally. The Nepal government implemented a strict lockdown to stop the spread of this viral infection. Objectives: Analyzing the impact of COVID-19-induced lockdowns in the pattern of dermatological diseases in comparison to the non-COVID period of 2019. Materials and methods: A retrospective cross-sectional study was done by reviewing the data from dermatology out-patients records for four months of each lockdown and four months of the non-COVID period. Results: There was a 49% and 7% reduction in visits of dermatology outpatients during the first and second lockdown, respectively compared to the pre-COVID period. The number of non-infectious diseases was more compared to infectious diseases. Bacterial infection decreased by 1%. Herpes zoster and scabies increased by 0.5-1% during lockdowns. Cases of eczema and urticaria increased by 2% and 3-5.5% during the first and second lockdowns, respectively. Papular urticaria and sexually transmitted infections decreased by 1% during the second lockdown. Consultations for melasma increased by 1.5%. Conclusion: There was a reduction in patient visits during both lockdowns. However, a marked reduction was seen during the first lockdown compared to the pre-COVID period. Pruritic conditions like eczemas, urticarias, and scabies increased, whereas papular urticaria decreased. Pigmentary disorders decreased, but visits for melasma increased. All bacterial infections decreased, whereas herpes zoster increased among viral infections. Chronic diseases like psoriasis and acne vulgaris decreased slightly. The number of sexually transmitted infections (STIs) also decreased. There was no difference in the proportion of infectious and non-infectious diseases compared to the pre-COVID and the lockdown periods.